2020
DOI: 10.1186/s12866-020-01841-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and metabolomic profiles in correlation with depression and anxiety co-morbidities in diarrhoea-predominant IBS patients

Abstract: Background: Psychological co-morbidities in irritable bowel syndrome (IBS) have been widely recognized, whereas less is known regarding the role of gut microbial and host metabolic changes in clinical and psychological symptoms in IBS. Results: A total of 70 diarrhoea-predominant IBS (IBS-D) patients and 46 healthy controls were enrolled in this study. Stool and urine samples were collected from both groups for 16S rRNA gene sequencing and metabolomic analysis. The results showed that fecal microbiota in IBS-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 86 publications
1
29
0
Order By: Relevance
“…Sequencing data of four non-CRC studies were utilized to evaluate the specificity of adenoma features. These four data sets were generated from patients who suffered from diseases other than CRC: PRJNA82111 43 , PRJNA544721 44 , PRJEB28350 45 , and PRJNA541332 46 (Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing data of four non-CRC studies were utilized to evaluate the specificity of adenoma features. These four data sets were generated from patients who suffered from diseases other than CRC: PRJNA82111 43 , PRJNA544721 44 , PRJEB28350 45 , and PRJNA541332 46 (Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have described an altered composition of gut microbiota and metabolites in several diseases of the GI tract such as colorectal cancer and inflammatory bowel disease [11,12]. In addition, IBS has been linked to an unbalanced gut microbiota profile [13][14][15][16] and possibly also to an altered metabolite profile [17,18], with links to GI [17,19] and psychological symptoms [20], at least in subsets of patients. There are also contradictory reports of lower, as well as higher, concentrations of faecal short-chain fatty acids in IBS with diarrhoea (IBS-D) as compared to healthy subjects [21].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the critical position of the gut microbiome in BAs synthetic regulation, gut dysbiosis may lead to dysmetabolism of BAs[ 14 ]. Ample evidence has suggested that the gut microbiota of IBS-D patients differs from that of healthy controls (HCs)[ 17 - 21 ], and gut dysbiosis has been considered to be involved in the putative pathophysiology of IBS[ 22 - 24 ]. However, information about correlations between fecal BAs and the gut flora in IBS-D patients is limited.…”
Section: Introductionmentioning
confidence: 99%